2017
DOI: 10.1248/bpb.b17-00316
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite Activates 5′AMP-Activated Protein Kinase-Endothelial Nitric Oxide Synthase Pathway in Human Glomerular Endothelial Cells

Abstract: Recent studies have shown that orally supplied nitrates, which substantially exist in our daily diets, are reduced into nitrites and become significant sources of nitric oxide (NO) especially in hypoxic tissues. However, physiological significance of nitrites in normal tissues has not been elucidated though our serum concentrations of nitrites reach as high as micromolar levels. We investigated effects of nitrite on endothelial NO synthase (eNOS) using human glomerular endothelial cells to reveal potential glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“… 43 The increased adiponectin induces insulin sensitivity in skeletal muscles by binding with adiponectin receptor type 1 and 2, leading to the activation of various signaling pathways such as IRS-1/2, AMPK, and p38 Mitogen-Activated Protein Kinase (p38–MAPK). 44 Also adiponectin alters nitric oxide level and leads to vasoprotective effects via activating AMPK 45 and cyclooxygenase II. 46 Moreover, adiponectin alleviates the inflammatory responses by inhibiting Tumor Necrosis Factor-Alpha (TNF-α), Interleukin-6 (IL-6), Interleukin-10 (IL-10), and Interleukin-1 (IL-1), 42 via Nuclear Factor Kappa-Light-Chain-Enhancer of Activated B Cells (NF-κB), and Protein Kinase A (PKA).…”
Section: Introductionmentioning
confidence: 99%
“… 43 The increased adiponectin induces insulin sensitivity in skeletal muscles by binding with adiponectin receptor type 1 and 2, leading to the activation of various signaling pathways such as IRS-1/2, AMPK, and p38 Mitogen-Activated Protein Kinase (p38–MAPK). 44 Also adiponectin alters nitric oxide level and leads to vasoprotective effects via activating AMPK 45 and cyclooxygenase II. 46 Moreover, adiponectin alleviates the inflammatory responses by inhibiting Tumor Necrosis Factor-Alpha (TNF-α), Interleukin-6 (IL-6), Interleukin-10 (IL-10), and Interleukin-1 (IL-1), 42 via Nuclear Factor Kappa-Light-Chain-Enhancer of Activated B Cells (NF-κB), and Protein Kinase A (PKA).…”
Section: Introductionmentioning
confidence: 99%
“…The reason explaining this difference remains to be elucidated. It is possible that nitrite, which is known to be an endogenous NO donor and an endogenous NO production enhancer, is unable to further increase NO beyond a plateau in endogenous NO production in tumoral endothelial cells after UTMC stimulation. It is also possible that tumor vessels treated with UTMC are already close to maximal dilation, in which case adding vasodilating agents could have little or no effect on the blood flow: this effect could be a consequence of the high levels of adenosine in tumor microenvironment, which is known to be a prominent vasodilator. , This could explain the increase in perfusion observed in tumors treated at 750 kPa (1 MHz) + nitrite to a plateau of endogenous NO production or to a maximum dilation, and why there is no difference between the perfusion values of tumors treated with SONOS alone and those treated with SONOS + nitrite (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was recently shown that UTMC combined with a sodium nitrite coinjection further increased the microvascular blood volume in muscle by 6–8 folds . Since nitrite is a nitric oxide (NO) donor in hypoxic and acidic environments , and can enhance endogenous NO production, we hypothesized that UTMC and nitrite could be synergistic as a spatially targeted provascular therapy in combination with RT in solid tumors. To the best of our knowledge, this effect of increasing perfusion by UTMC has never been validated in the tumor, nor has it been combined with subsequent RT.…”
Section: Introductionmentioning
confidence: 99%